ASPECTS OF EFFECTIVE USER INTERFACE DESIGN OF DEMONSTRATION ENVIRONMENT COMPONENTS (Journal of Information Technologies in Education (ITE), 2011)
We analyzed question of the studying course "Basics of algorithmization and programming". We propose to study material by using program demonstration environment. We described the perspectives of effective design of software application in the future.
Keywords: informatization; information and communication technologies; the program demonstration environment; Vìdeoìntepretator; user interface; design